2010
DOI: 10.1111/j.1559-1816.2009.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Tipping Motivations and Behavior in the U.S. and Israel

Abstract: Tipping is a multi-billion dollar phenomenon and a major source of income for millions of workers. The results of a study conducted in the US and Israel suggest that people tip mainly to show gratitude, conform to the social norm, and because they know that waiters' income depends on tips.Tipping is motivated more by the positive consequences of tipping than by the negative results of not tipping. Patronage frequency and dining alone have no systematic effects on the level of tips or their sensitivity to servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 44 publications
8
74
1
Order By: Relevance
“…Because the service has already been provided by the time the tip is given, the service provider can no longer change the service in response to the tip. Empirical studies, however, show that almost all people tip where this is a social norm (Azar, 2006b). Consequently, tipping is an example that illustrates the importance of social norms and psychological motivations in economic behavior (Azar, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Because the service has already been provided by the time the tip is given, the service provider can no longer change the service in response to the tip. Empirical studies, however, show that almost all people tip where this is a social norm (Azar, 2006b). Consequently, tipping is an example that illustrates the importance of social norms and psychological motivations in economic behavior (Azar, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…This result is rather surprising-all previous studies found either no relationship or a positive relationship (which would be in line with the economic theory). One explanation of this striking result may be that in fact there is no relationship between the patronage frequency and the gratuity size, and the relationship found in some previous studies is a result of a missing covariate, see Azar (2010a). Thus regular patrons tip more or less than the occasional customers because they belong to a different social group, not because of any strategic reasons.…”
Section: Figure 1 Empirical Distribution Of Gratuity In the Data Samplementioning
confidence: 86%
“…The tipping norms are slightly lower both in Canada, see e.g. Bodvarsson and Gibson (1999), and in Israel, see Azar (2010a).…”
Section: Literature Reviewmentioning
confidence: 98%
See 2 more Smart Citations